2001
DOI: 10.1002/ajmg.1477
|View full text |Cite
|
Sign up to set email alerts
|

PTEN mutation in a family with Cowden syndrome and autism

Abstract: We report on a mother and son with Cowden syndrome and a PTEN mutation. The boy also exhibits autistic behavior and mental retardation, while his mother has a normal intelligence and social interaction pattern. We review the scanty literature data on the association of Cowden syndrome and autism and emphasize that the association of progressive macrocephaly and pervasive developmental disorder seems to be an indication for screening for PTEN mutations.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
140
0

Year Published

2002
2002
2020
2020

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 198 publications
(142 citation statements)
references
References 28 publications
2
140
0
Order By: Relevance
“…61 The phenotype in the mother was Cowden syndrome. The child, too, had Cowden syndrome but also had an ASD.…”
Section: Single-gene Disordersmentioning
confidence: 99%
“…61 The phenotype in the mother was Cowden syndrome. The child, too, had Cowden syndrome but also had an ASD.…”
Section: Single-gene Disordersmentioning
confidence: 99%
“…Macrocephaly is common and several studies have identified autism or autistic behaviors in PHTS patients with this feature (Goffin et al, 2001;Butler et al, 2005). It is unclear why the neurological phenotypes associated with PHTS are so highly variable.…”
Section: Germline Mutations Of Pten Cause Neurological Abnormalitiesmentioning
confidence: 99%
“…A well-established candidate gene is the tumor-suppressor gene, phosphatase and tensin homolog missing on chromosome 10 (PTEN) (4)(5)(6)(7). Pten is a lipid and protein phosphatase best known for its role in suppressing tumor formation by inhibiting cellular survival, proliferation, and cellular architecture (8,9), but which also plays an important role in brain morphology and synaptic function (10,11).…”
mentioning
confidence: 99%
“…Pten acts via its lipid phosphatase activity to dephosphorylate phosphatidylinositol (3,4,5)-trisphosphate and negatively regulate the PI3K-mammalian target of rapamycin (mTOR) signaling pathway. Although PTEN mutations are present in 5-10% of people with ASDs (12)(13)(14), loss-of-function point mutations in this gene give rise to progressive macrocephaly, a hallmark feature that occurs in nearly 20% of humans with ASDs (5,6). In addition to anatomical abnormalities, humans with inactivating PTEN mutations exhibit spontaneous seizures and deficits in social and cognitive behaviors (10,11).…”
mentioning
confidence: 99%